Genetic variability and differentiation of rainbow trout strains in Iran - YOUSEFIAN, MEHDI (The Indian Journal of Animal Sciences, 2016)
To determine the genetic structure and differences of rainbow trout, variations in 9 microsatellite loci in four stocks of rainbow trout from Mazandran, Iran were examined. Three samples were introduced from Norwegian, French stocks, and one was from Iranian stocks rearing in North of Iran. Most but not all loci were polymorphic in all stocks. There was substantial genetic differentiation among populations, with an average FST value of 0.065. The four stocks averaged 5.2–7.4 alleles per locus, with average heterozygosities of around 0.625 to 0.762. A large variation in observed hetrozygocity, averaged over all samples was observed among loci and ranged from 0.015 in OTSG474 to 0.850 in OTSG249. Nine of 20 tests for Hardy – Weinberg expectations gave significant deviations. The cause(s) of these deviations are unknown. The Norway strain was significant deviations from HWE in all 5 polymorphic loci. The degree of differentiation among strain or Nei Genetic Distance compared pairwise accorded well with their likely genetic connectivity. Two of the strains, Iranian and Norway had the highest Nei Genetic Distance (0.213) and were different in all loci except for OTSG3. The level of genetic variation in the domesticated rainbow trout strains that are farmed in European countries (French, Norway) and Iran did not differ significantly neither within nor between the countries, but the highest pronounced difference was comparable with that of the Norway and Iran strains.